(untitled) (Faridpur Medical College Journal, 2014)
This cross sectional study was carried out at Bangabandhu Sheikh Mujib Medical University (BSMMU) and International Centre for Diarrhoeal Disease Research, Bangladesh (ICDDR,B) from July 2008 to September 2009. Aim of the study was to find out the antimicrobial susceptibility profile of Helicobacter pylori isolates from dyspeptic patients. Total 224 dyspeptic patients from Out Patient Department (OPD) of BSMMU were initially enrolled after informed written consent. After upper GI endoscopy 157 patients were finally included who had erosions, ulcers or atrophic changes in the stomach or duodenum. Two biopsy samples were taken from each of them. Samples were incubated at 37°C in a double gas incubator with 5%O2, 10%CO2 and 85%N2. Total 82 (52.23%) samples were found positive for H. pylori. Isolated organisms were then tested for sensitivity to Amoxicillin, Clarithromycin, Tetracycline, Levofloxacin and Metronidazole by Agar dilution method. Among 82 patients 51(62.2%) were male and 31(37.8) were female with a male:female ratio 1.6:1. Patients were categorized into two groups one having gastric or duodenal ulcer (30.5%) and other having no ulcer (69.5%). Among these isolates 92.7% were sensitive to Amoxicillin, 89% to Clarithromycin, 81.7% to Tetracycline, 80.5% to Levofloxacin and only 26.8% to Metronidazole. Beside these, 81.7% isolates were sensitive to both Amoxicillin and Clarithromycin, 74.4% to Amoxicillin and Tetracycline, 73.2% to Amoxicillin and Levofloxacin, 72% to Clarithromycin and Tetracycline, 59% to Clarithromycin and Levofloxacin and 51% to Tetracycline and Levofloxacin DOI: http://dx.doi.org/10.3329/fmcj.v8i2.20280 Faridpur Med. Coll. J. 2013;8(2): 49-52